Pituitary tumours in the elderly: a 20 year experience. - Turner, H; Adams, C; Wass, J (1999)
The proportion of the elderly in the population is increasing, and the appreciation and management of medical problems in this age group will therefore become more important. We therefore decided to determine the clinical features and types of pituitary tumour presenting in the elderly, and to examine the treatment and outcome in this group. We conducted a retrospective case-note review from a specialist endocrine and neurosurgical unit in a tertiary referral centre. Eighty-four patients aged 65 years and over on diagnosis of a pituitary tumour were referred to the unit between 1975 and 1996. There were 45 males and 39 females, and the mean age was 72.4 years (range 65-86). Over half of the pituitary lesions were non-functioning adenomas (NFAs) (60.7%). GH-secreting tumours were present in 11 (13.1%) and macroprolactinomas in 7 (8.1%). Four patients had microadenomas and 17 had miscellaneous pituitary-related lesions. Visual deterioration was the commonest mode of presentation in 33 (39.3%), but 54 (64.3%) had evidence of visual impairment on detailed examination. Despite the majority of patients (80.8%) having coexisting medical conditions, trans-sphenoidal surgery was performed in 60 (71.4%) and was well tolerated with a zero peri- and post-operative mortality rate, and post-operative complications in 11 (13.1%). Pituitary tumours in the elderly are most frequently NFAs that present with visual deterioration and hypopituitarism. The fact that 46.5% were pan-hypopituitary on diagnosis and that 64.3% of patients had visual impairment suggests a delay in diagnosis in this age group. Despite significant coexisting medical pathology in this large series of patients, surgery was safe and successful in the majority.